2019
DOI: 10.4103/ijpsym.ijpsym_461_18
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders: An Overview of Indian Research

Abstract: There has been sporadic research on eating disorders in India, with no published attempt to collate and summarize the literature landscape. Hence, the present narrative review aims to summarize Indian work related to eating disorders, discern current trends, and highlight gaps in research that will provide directions for future work in the area. Electronic search using the MEDLINE, Google Scholar, and PsycINFO databases was done to identify relevant peer-reviewed English language articles, in October 2018, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 44 publications
(109 reference statements)
0
45
1
1
Order By: Relevance
“…This study sheds new light on the risk factors of eating disorders and also reports a significant association between body shape concerns, stress, and eating disorders, which has not been assessed in the Indian population [27]. But one limitation of the study is that this is done in a single institution which might be limiting the generalizability.…”
Section: Discussionmentioning
confidence: 90%
“…This study sheds new light on the risk factors of eating disorders and also reports a significant association between body shape concerns, stress, and eating disorders, which has not been assessed in the Indian population [27]. But one limitation of the study is that this is done in a single institution which might be limiting the generalizability.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, in a sample of treatment-seeking SA adolescents in the United Kingdom, Tareen and colleagues (2005) found that, although their patients exhibited many typical anorexia nervosa (AN) symptoms, (e.g., loss of appetite), they did not endorse fat phobia or extreme weight preoccupation. Similar "non-fat phobic" AN presentations have been documented on the Indian subcontinent and in other Asian regions (Nakai et al, 2021;Pike & Dunne, 2015;Vaidyanathan et al, 2019). While certain symptoms can be difficult to assess for all populations (e.g., compulsive exercise; Hockin-Boyers & Warin, 2021), it is possible that some "typical" ED features might be completely absent, manifest differently, or considered socially acceptable in SAs (Kawamura, 2015).…”
mentioning
confidence: 75%
“…3 One study showed that 16% of people with schizophrenia had binge eating disorder, 4 and in China, Japan, Africa, and Latin America, binge eating disorder had the highest prevalence among all eating disorders, although no cases were reported in India. 5 In India, the most common psychiatric comorbidity (50%) observed in patients with an eating disorder was depression. 5 Here, we present an interesting case of schizophrenia in a patient whose psychotic features were under control, but her eating habits were worrisome and prompted consultation.…”
Section: Introductionmentioning
confidence: 99%
“…5 In India, the most common psychiatric comorbidity (50%) observed in patients with an eating disorder was depression. 5 Here, we present an interesting case of schizophrenia in a patient whose psychotic features were under control, but her eating habits were worrisome and prompted consultation. 1 every 3 hours and once during the nighttime; approximate calories, 1,500-1,700 per day.…”
Section: Introductionmentioning
confidence: 99%